Przemiany osadnicze w międzyrzeczu rzek Szkło i Lubaczówki w epoce brązu i wczesnej epoce żelaza - Jabłkowska, Aleksandra (Muzeum Okręgowe w Rzeszowie, 2020)
The article is a settlement and culture study, in which, after collecting all available sources and their chronological verification, a deep analysis of habitat preferences was carried out in individual cultural units in the area of the Szkło and Lubaczówka rivers in the Bronze Age and the Early Iron Age. The research performed on settlement and culture study aims to show new results and fill the gap existing in the literature within the San basin in terms of understanding the cultural and settlement variability in the Bronze Age and the Early Iron Age (other neighbouring mesoregions already have such studies).

Settlement studies, which are the aim of this article, constitute the basic analytical method to research the changes in the development of settlement of a given area in a particular period of time. The main goal of the research presented here is the analysis and reconstruction of settlement changes in the basin of the Szkło and Lubaczowka rivers in the Bronze Age and the Early Iron Age. The northern border of the area is the course of the Lubaczowka river. From the south, the research area is closed by the Szkło river, whereas the western border is located along the San River. As for the east, the analysed area is limited by the eastern border of Poland. The chronological range includes the Bronze Age and the Early Iron Age. On the basis of the collected source material, it was possible to distinguish four cultural units in the discussed area in the period of our interests, i.e. the Mierzanowice culture (KM), the Trzciniec culture (KT), the Tarnobrzeg Lusatian culture (TKŁ) and the Pomeranian culture (KPM). In addition to them, eastern influences were observed in the form of ceramics associated with the Scythian cultural circle and two fragments of graphite ceramics representing the La Tene culture. The source database consists of information obtained during the archival research of the Polish Archaeological Record (AZP) cards in the Archives of the Voivodeship Heritage Monuments Protection Office in Przemyśl. They were additionally supplemented with research results obtained in the course of excavations and published in the literature. Such information was gained only for three sites: Wietlin III 1, Jarosław district, Wolka Krowicka 3, district Lubaczow district and Łazy 30, Jarosław district. In the basin of the Szkło and Lubaczowka rivers, the distribution of settlement points representing individual cultures of the Bronze Age and the Early Iron Age is quite uneven. However, in some areas, the remains of settlements are concentrated to form clearly visible settlement clusters. In order to determine them, one of the method so-called an analysis of the territory exploited by the settlement was implemented in order to determine and restore the concentration and density of settlement points of individual archaeological cultures of the Bronze Age and the Early Iron Age in the basin of the Szkło and Lubaczowka rivers. The first stage of settlement development in the basin of the Szkło and Lubaczowka rivers in the Bronze Age and the Early Iron Age is associated with the Mierzanowice culture. Regarding the settlement points of this cultural unit, it is possible to distinguish settlements (21 sites) and traces of settlement (63 sites). On the other hand, not a single cemetery of the discussed culture has been registered in the area of the basin of the Szkło and Lubaczowka rivers. The second stage of settlement changes is connected with the Old Bronze Age, which is represented by the Trzciniec culture. In the case of this culture, taking into account the basin of the Szkło and Lubaczowka rivers, we can distinguish 24 sites recognized as settlements and 41 traces of settlement. We likewise in the early Bronze Age culture, do not record a single cemetery in the aforementioned area. After the periods of existence and development of Early and Older Bronze Age cultures, when the settlement was characterized by a significant dispersion of sites and a lower density, this picture has changed since the Middle Bronze Age. The settlement was continued by the community of the Tarnobrzeg Lusatian culture from. The aforementioned cultural unit was represented in the basin of the Szkło and Lubaczowka rivers by 2 cremation cemeteries, 48 settlements and 96 settlement traces. The last stage of settlement transformations in the basin of the Szkło and Lubaczowka rivers was the appearance of the Pomeranian culture. On the basis of the small number of sites in the basin of the Szkło and Lubaczowka rivers, it is not possible to determine the settlement structure characteristic of the Pomeranian culture. It is only possible to conclude that during that period there was a significant dispersion and decrease in the density of settlement of the discussed area with references to the population of the Pomeranian culture. On the other hand, they should not be treated as signs of a regression of settlement in the basin of the Szkło and Lubaczowka rivers. It is worth noting the location of the settlement points of particular cultures in relation to various environmental parameters. Based on the conducted analyses, it can be concluded that the discussed area of the Szkło and Lubaczowka rivers is characterized by low environmental diversity, therefore the parameters of the areas occupied and exploited by individual cultures of the Bronze Age and Early Iron Age are similar to each other.
Settlement transformations in the basins of the Szkło and Lubaczówka rivers in the Bronze Age and the Early Iron Age
Niniejsze opracowanie jest nieznacznie zmienioną wersją pracy magisterskiej napisanej pod kierunkiem prof. dr. hab. Sylwestra Czopka i obronionej na Wydziale Socjologiczno-Historycznym Uniwersytetu Rzeszowskiego w 2019 roku.
Keywords: Bronze Age; Early Iron Age; settlement archaeology; south-eastern Poland